THE PRESENT-VALUE METHOD AND THE REPLACEMENT DECISION. - Moore, Carl L. (The Accounting Review, 1964)
Abstract Frequently, the decision to replace or not to replace a plant asset is handled as a separate problem and is not included as a part of the general capital investment problem. This separation has probably resulted in part from the attention given to replacement decisions in engineering economy studies. Engineering studies are made to determine which units of equipment can give the best service at the lowest possible costs. Equipment in operation is in constant competition with new and improved models as they become available on the market and at some point in the life of a piece of equipment replacement may bring about the desired performance at a minimum annual cost. The objective in many replacement studies is to time the replacements so that annual costs will be minimized. The replacement type of decision is also isolated from general capital investment planning because of a difference in point of view that may be attributable to a difference in the level of administrative control. In replacement studies the equipment cost, the future costs of operation and the future salvage values are carefully estimated and applied in an effort to hold costs to a minimum.